The Qur'an as a Guide to Creating Harmony in Multicultural Societies - Ma'wa, Izzatul; Yumna, Riqqotul; Ichwan, Moh. Nor (Department of Anthropology, 2025)
This study explores the role of harmony in multicultural societies and how the values contained in the Quran can contribute to creating a harmonious environment. The issues investigated include the challenges multicultural communities face, such as the potential for conflict and discrimination, and the importance of building respectful relationships among diverse cultural, religious, and ethnic backgrounds. The research design employs a qualitative approach with content analysis of relevant Quranic texts alongside in-depth interviews with community leaders and religious figures. The analysis results indicate that values of harmony, such as tolerance, mutual respect, and cooperation, are strongly emphasized in the Quran. The main findings also suggest that applying these values in daily life can reduce group tensions and foster positive collaboration. Additionally, communities that embrace the principles of harmony tend to be more socially and economically stable, attracting investment and creating job opportunities. In the author's interpretation, the significance of harmony in multicultural societies is not only relevant in the context of conflict avoidance but also as a key to sustainable development. The author concludes that by prioritizing Quranic values in social interactions, communities can create a safe and inclusive environment where every individual feels valued and can contribute positively. This research provides important insights for efforts to build stronger and more united communities in the era of globalization.Abstrak: Penelitian ini mengeksplorasi peran kerukunan dalam masyarakat multikultural dan bagaimana nilai-nilai yang terkandung dalam Al Qur'an dapat berkontribusi dalam menciptakan lingkungan yang harmonis. Isu yang diteliti meliputi tantangan yang dihadapi masyarakat multikultural, seperti potensi konflik dan diskriminasi, dan pentingnya membangun hubungan yang saling menghormati di antara berbagai latar belakang budaya, agama, dan etnis. Desain penelitian menggunakan pendekatan kualitatif dengan analisis isi teks-teks Al-Qur'an yang relevan serta wawancara mendalam dengan para pemimpin masyarakat dan tokoh agama. Hasil analisis menunjukkan bahwa nilai-nilai kerukunan, seperti toleransi, saling menghormati, dan kerja sama, sangat ditekankan dalam Alquran. Temuan utama menunjukkan bahwa penerapan nilai-nilai ini dalam kehidupan sehari-hari dapat mengurangi ketegangan kelompok dan mendorong kolaborasi yang positif. Selain itu, masyarakat yang menganut prinsip-prinsip kerukunan cenderung lebih stabil secara sosial dan ekonomi, menarik investasi dan menciptakan lapangan pekerjaan. Menurut interpretasi penulis, pentingnya kerukunan dalam masyarakat multikultural tidak hanya relevan dalam konteks penghindaran konflik, tetapi juga sebagai kunci pembangunan berkelanjutan. Penulis menyimpulkan bahwa dengan mengedepankan nilai-nilai Qur'ani dalam interaksi sosial, masyarakat dapat menciptakan lingkungan yang aman dan inklusif di mana setiap individu merasa dihargai dan dapat berkontribusi secara positif. Penelitian ini memberikan wawasan penting bagi upaya membangun masyarakat yang lebih kuat dan bersatu di era globalisasi.